Evaluasi Kualitas Layanan Sistem Informasi Penduduk Menggunakan Metode E-Govqual Dan IPA (Studi Kasus Pada Dinas Kependudukan Dan Pencatatan Sipil Kota Pasuruan) - Nerissa Arviana Zagita; Himawat Aryadita; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Instruction_President number_3 of 2003_about the national policies and strategies for the development of e-government services (e-government) make The Departement of Population and Civil Registration Pasuruan City follow development by providing services in the form of website Population Information System. Every public service (an interested person) needs to be evaluated on a scale of every year for the purpose of optimizing service. The purpose of this research is to know the assessment of quality of website service of Pasuruan City Population Information System according to user_using dimension of e-govqual and Importance_Performance_Analysis (IPA), determining which attributes become priority in improving service quality obtained from IPA analysis result and giving recommendation from analysis attribute at dimension e-govqual._The user data is derived from the spread of the questionnaire distributed to 43 respondents who will be sampled on the research, the results of the analysis of Importance_Performance_Analysis on the level of conformity_a value <100% and the value of the gap of less than 0 (gap <0) of each dimension in e-Govqual, the performance of the website services has not been able to meet the wishes / expectations0users. From the results of the IPA quadrant analysis there are 6 atributes is a main priority improvement as well as 6 attributes that constitute a low priority improvement. Of the twelve attributes, there will be a recommendation for improvement based on the literature or theories on the attributes required to improve the quality of website services.